Efficacy and safety of raltitrexed plus S-1 versus regorafenib in patients with refractory metastatic colorectal cancer: a real-world propensity score matching study. (May 2022) - Zhou, Yu-Wen; Wang, Jia-Ling; Li, Qing-Fang; He, Yuan-Lin; Li, Lin-Juan; Liu, Rui-Zhi; Chen, Ye; Zhang, Shuang; Qiu, Meng; Liu, Ji-Yan
Background: Raltitrexed plus S-1 (RS) and regorafenib both showed considerable efficacy for metastatic colorectal cancer (mCRC) patients. This study aims to compare the effectiveness and safety of two different regimens in patients with refractory mCRC. Methods: This retrospective cohort study included mCRC patients who were treated with RS or regorafenib from February 2017 to June 2021. A propensity score matching (PSM) analysis was conducted to balance the baseline characteristics of all patients. Progression-free survival (PFS), overall survival (OS), tumor response, and safety of two regimens were evaluated. Results: A total of 187 patients were included in our study, with 107 patients in the RS group and 80 patients in the regorafenib group. After PSM, 78 pairs were recognized. Patients treated with RS had a semblable PFS compared to those treated with regorafenib before PSM (4.8 months vs 5.5 months, p  = 0.400) and after PSM (4.7 months vs 5.4 months, p  = 0.430). Patients in the RS group were associated with a longer OS than those in the regorafenib group (13.4 months vs 10.1 months, p  = 0.010). A similar trend of OS was also obtained in the matched cohort (13.3 months vs 10.0 months, p  = 0.024). Both objective response rate (12.8% vs 5.1%, p  = 0.093) and disease control rate (53.8% vs 46.2%, p  = 0.337) in the RS cohort were higher than those in the regorafenib group, without significant differences. Adverse events (AEs) of each group were well tolerated. Conclusion: Patients treated with RS demonstrated a longer OS than those treated with regorafenib and had manageable AEs, which could be recognized as a primary choice for refractory mCRC. Plain Language Summary: Efficacy and Safety of Raltitrexed plus S-1 Versus Regorafenib in Patients with Refractory Metastatic Colorectal Cancer: A Real -world Propensity Score Matching Study Both raltitrexed plus S-1 (RS) and regorafenib showed considerable efficacy for metastatic colorectal cancer (mCRC) patients. No study has compared the two regimens yet. Therefore, we compare the efficacy and safety between RS and regorafenib to provide an optimal treatment option. We retrospectively included patients with mCRC who failed at least two standard treatments. All enrolled patients received RS or regorafenib treatments. We conducted a propensity score matching to eliminate differences in the enrolled patients. After the analysis, we found no significant differences in progression-free survival in patients between the two groups. However, patients treated with RS had a longer OS than those treated with regorafenib, whether before matching (13.4 months vs 10.1 months, p  = 0.010) or after matching (13.3 months vs 10.0 months, p  = 0.024). In addition, the adverse effects caused by cancer-related therapy were tolerable for the patient. Certainly, this is a non-randomized retrospective study with a small sample size, so we conducted a propensity score matching to minimize potential bias. Importantly, this is the first research comparing the two treatments, and we believe that the results of this article could present a primary choice for clinical doctors dealing with patients with standard treatments that failed mCRC.